Tropical Root Crop Production in Florida - Mary Lamberts; Stephen M. Olson (EDIS)
There are four main tropical root crops produced in Florida. These are: cassava, tannia, taro and boniato. This document is HS965, Horticultural Sciences Department, UF/IFAS, Florida Cooperative Extenstion Service, September 2004.